Does malaria affect placental development? Evidence from in vitro models. - Alexandra J Umbers; Danielle I Stanisic; Maria Ome; Regina Wangnapi; Sarah Hanieh; Holger W Unger; Leanne J Robinson; Elvin Lufele; Francesca Baiwog; Peter M Siba; Christopher L King; James G Beeson; et al. (PLoS ONE, 2013)
BACKGROUND:Malaria in early pregnancy is difficult to study but has recently been associated with fetal growth restriction (FGR). The pathogenic mechanisms underlying malarial FGR are poorly characterized, but may include impaired placental development. We used in vitro methods that model migration and invasion of placental trophoblast into the uterine wall to investigate whether soluble factors released into maternal blood in malaria infection might impair placental development. Because trophoblast invasion is enhanced by a number of hormones and chemokines, and is inhibited by pro-inflammatory cytokines, many of which are dysregulated in malaria in pregnancy, we further compared concentrations of these factors in blood between malaria-infected and uninfected pregnancies. METHODOLOGY/PRINCIPAL FINDINGS:We measured trophoblast invasion, migration and viability in response to treatment with serum or plasma from two independent cohorts of Papua New Guinean women infected with Plasmodium falciparum or Plasmodium vivax in early pregnancy. Compared to uninfected women, serum and plasma from women with P. falciparum reduced trophoblast invasion (P = .06) and migration (P = .004). P. vivax infection did not alter trophoblast migration (P = .64). The P. falciparum-specific negative effect on placental development was independent of trophoblast viability, but associated with high-density infections. Serum from P. falciparum infected women tended to have lower levels of trophoblast invasion promoting hormones and factors and higher levels of invasion-inhibitory inflammatory factors. CONCLUSION/SIGNIFICANCE:We demonstrate that in vitro models of placental development can be adapted to indirectly study the impact of malaria in early pregnancy. These infections could result in impaired trophoblast invasion with reduced transformation of maternal spiral arteries due to maternal hormonal and inflammatory disturbances, which may contribute to FGR by limiting the delivery of maternal blood to the placenta. Future prevention strategies for malaria in pregnancy should include protection in the first half of pregnancy.